Učitelji geografije v poklicnih biografijah o vplivih na svoj profesionalni razvoj - Konečnik Kotnik, Eva; Javornik Krečič, Marija (Revija za elementarno izobraževanje, 2011)
Assessing the Professional Development of Geography Teachers by Use of Autobiographies. In the article we present some geography teachers’ reflections about what influences their professional development. In the first part we briefly present some factors which influence teachers’ professional development. In the continuation we present the results of our qualitative empirical research, carried out between September and October 2010. The basic intention of the research was to get insight into geography teachers’ reflections about the influences on their professional development by use of autobiographies. The results show that we can identify phases and factors of professional development from professional autobiographies, which we define in the first part of our article. The results can be helpful in developing support for teacher work.